In defense of a joyful positivism Michel Foucault in file (2012)
This paper intends to relect on the use of theories and methods in social sciences and history. For many authors these two components seemed irreconcilable inthe development of a research work, it looked like some used the theory, while the work of others was to compile the ile information. This was made throughout thetwentieth Century, history and social sciences wandered off between formal concepts and data collection, leaving huge gaps in the research process. In that vein, thecontributions of Michel Foucault are important in his dedication to the ile and the theoretical analysis of social reality, which have allowed him to explain other realitiesthat were out of traditional structures. In this way, the method gets closer to the relections about language and culture, which provides innovative aspects in thetreatment of society and, especially of human groups that are out of the “normal” context of society.